Compensating Nuclear Damage in China - Liu Jing; Michael Faure (Washington University Global Studies Law Review, 2012)
The goal of this article is to address the Chinese compensation regulatory regime for nuclear accidents, particularly regarding nuclear liability. A full discussion of the Chinese nuclear regulatory framework and liability system is beyond the scope of this article. This article primarily focuses on the compensation system for nuclear damage in China. Part II of this article provides a short history of China’s nuclear policy and its existing nuclear energy regulatory framework. Part III discusses the legislative framework for liability and the effectiveness of the two critical government documents that regulate nuclear liability in China: the “Reply to the Ministry of Nuclear Industry, the National Nuclear Safety Bureau and the State Council Atomic Energy Board in respect of Handling Nuclear Third Party Liability” published in 1986 (the “1986 Reply”), and the “Reply to Questions on the Liabilities of Compensation for Damages Resulting from Nuclear Accident” (the “2007 Reply”). Part IV then discusses in more detail the rules dealing with nuclear liability in China. Part V provides a critical evaluation and comparison of the nuclear liability framework in China, contrasting it to some nuclear liability economic starting points and to the nuclear liability regime under the U.S. Price-Anderson Act and international conventions. Part VI concludes the article.
Keywords: fukushima; nuclear policies; compensation; remedies